2021
DOI: 10.2147/cmar.s321225
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Application of Salivary Exosomes in Malignant Neoplasms

Abstract: The study of salivary exosomes in malignant neoplasms has attracted widespread attention in the clinical setting. Although a variety of diagnostic and treatment approaches have been proposed, there are some limitations to their application. In recent years, the role of salivary exosomes in cancer has been increasingly studied. Salivary exosomes not only renew and regulate the biological behavior of tumor cells, such as malignant proliferation, migration, and invasion, but they also serve as ideal markers for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The results of these studies suggested that it may play a role in salivary gland tumor pathogenesis and prognosis [ 83 ]. Salivary exosomes could represent the foundation for the development of targeted tumor therapy [ 84 ]. Future clinical trials are needed for liquid biopsy to be used as a diagnostic tool in identifying these neoplasms [ 81 , 82 , 83 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The results of these studies suggested that it may play a role in salivary gland tumor pathogenesis and prognosis [ 83 ]. Salivary exosomes could represent the foundation for the development of targeted tumor therapy [ 84 ]. Future clinical trials are needed for liquid biopsy to be used as a diagnostic tool in identifying these neoplasms [ 81 , 82 , 83 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…257 Additionally, neurodegenerative diseases were given much attention for saliva exosome biomarker discovery. 258 There have been reviews summarizing salivary exosomal biomarkers in cancer, [259][260][261][262][263] neurodegenerative diseases, 264 mental diseases, 265 systematic disease, 266 wound healing 267,268 and isolation methods. 269,270 Research articles emphasize protein biomarkers 250,257,[271][272][273][274][275] and RNA markers.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%
“…Exosomes can be isolated from small amounts of saliva, because exosomes are found in abundance in saliva sample compared to other biological fluids. For instance, saliva is one of the most viscous body fluids in the human body due to its high mucin content, and the viscosity of unstimulated saliva is 5–7 centipoise, much greater than that of human plasma and serum which have just 1.65 and 1.4 centipoise of viscosity, respectively 21 . Besides, salivary exosomes have a robust stability and resistance to degradation in body fluids, due to their structural characteristics.…”
mentioning
confidence: 99%